Creative resources mobilized in the make-believe of children with intellectual disabilities - Abreu, Fabrício Santos Dias de (2023)
This study investigates the play of children with intellectual disabilities based on the Historical Cultural Theory with the purpose of questioning: the representation of roles; the substitutive use of support objects; and the participation of bodily resources in play. Through microgenetic research, with analysis of an episode that occurred in a Brazilian public school, it was verified that the participants' play involved the assumption of characters and the symbolization of objects to compose fictitious scenarios. These data indicate that this audience has a complex imaginative functioning but marked by specificities that deserve investigation.